Single women in Malaysia: perception of challenges and coping - Alwi, Azlin; Noor, Noraini M. (2016)
Single women’s issues and challenges are seldom the center of research. One of the factors is the invisibility of this group within the society. In Malaysia where the cultural emphasis is on family value and a sense of collectiveness, many still perceives being single as a deviation from the norm. As a result, many single women feel pressure to find spouses and settle down. Research has shown that single women face stigma, discrimination, and stereotyping. Despite this, there are many single women who defy society’s expectations, remain single and happy. This research attempts to provide an insight into the life of single women in Malaysia. The research is important because of a lack of literature on this particular population in the Malaysian context. Therefore, this study attempts to shed light onto their well-being. Specifically, the objectives of the study are to determine single women’s: (1) perception on marriage, work, and education; (2) resilience level; (3) religious motivation; (4) experience of major challenges; and (5) factors that can increase well-being. Using a purposive sampling and snowball method, 121 employed single women between the ages of 30 to 50 participated in this study. Results from this study indicated that women were single because they had not found a suitable candidate to marry, caring for parents, and negative past experiences. They also regarded career highly, in that they wanted to maintain their independence and status in the society. By attaining higher education, they believed they could be more confident, better decision maker, and be able to realize their dreams. They faced challenges attributed to fear for their safety, lack of emotional support, concerned with other people’s negative perception, and health-related illnesses. Factors that can increase coping include social and emotional support, religious strength, internal attributes, and active lifestyle.